3D Simulations of Blood Flow Dynamics in Compliant Vessels: Normal, Aneurysmal, and Stenotic Arteries (Communications in Computational Physics, 2020)
Arterial diseases such as aneurysm and stenosis may result from the mechanicaland/or morphological change of an arterial wall structure and correspondinglyaltered hemodynamics. The development of a 3D computational model of bloodflow can be useful to study the hemodynamics in major blood vessels and may providean insight into the noninvasive technique to detect arterial diseases in early stage.In this paper, we present a three-dimensional model of blood flow in the aorta, whichis based on the immersed boundary method to describe the interaction of blood flowwith the aortic wall. Our simulation results show that the hysteresis loop is evident inthe pressure-diameter relationship of the normal aorta when the arterial wall is consideredto be viscoelastic. In addition, it is shown that flow patterns and pressuredistributions are altered in response to the change of aortic morphology.